Self-implementation or FDIs in Hydropower Development: A Dilemma - Manandhar, Bhai Raja (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Not available. DOI: http://dx.doi.org/10.3126/hn.v16i0.12210 Hydro Nepal Journal of water, energy and environment Issue. 16, 2015, Page : 1-1 Upload date: March 1, 2015